Bjärsjöholm estate in the Early Modern Period A historical and archaeological analysis - Mazij,Katarzyna Maria (2024)
Bjärsjöholm is an estate located close to the coastal town of Ystad, around 4.5 km. The aim of this thesis was to gain insight into the changes and development that the change from Danish to Swedish rule of Scania meant for Bjärsjöholm estate. The research questions were: • How has the economy changed during the 16th, 17th and 18th century for the Bjärsjöholm estate? • What changes of the buildings at the estate occurred from the 16th to 18th century? • How did the estate and landscape history change on Bjärsjöholm in the 16th, 17th and 18th century? Previous research has mostly been on the Scanian towns and cities as well as the landscape and other estates. Sölve Johansson has done a project on Bjärsjöholm in 1992, besides that not much has previously been studied about the estate. The theory in this thesis has two perspectives, those are an economic perspective and a archaeology of building perspective, focusing on the estate and landscape history. The methods are mostly literature analysis and an analysis of maps in form of a qualitative and comparative method. Analysis of Bjärsjöholm estate between the 16th to 18th centuries revealed the changing economy of the estate. The landscape, economy and history of the building and foundation of Bjärsjöholm was analyzed. Both economy and landscape changed with an increase of the economy in the 16th century when the estate was built, then a larger decrease in the 17th century due to wars and decrease in trade, and finally a more peaceful time allowed for a better economy and development in the landscape and renovations of the estate in the 18th century which resulted in the estate’s land growing and the opening of a tannery.
Keywords: Bjärsjöholm; Early Modern Period; historical archaeology; Scania